A scoping review to determine the barriers and facilitators to initiation and performance of bystander cardiopulmonary resuscitation during emergency calls - Aldridge, Emogene; Perera, Niru; Ball, Stephen; Finn, Judith; Bray, Janet (2022)
Background: To maximise out-of-hospital cardiac arrest (OHCA) patients’ survival, bystanders should perform continuous, good quality cardiopul- monary resuscitation (CPR) until ambulance arrival. Objectives: To identify published literature describing barriers and facilitators between callers and call-takers, which affect initiation and perfor- mance (continuation and quality) of bystander CPR (B-CPR) throughout the OHCA emergency call. Eligibility criteria: Studies were included if they reported on the population (emergency callers and call-takers), concept (psychological, physical and communication barriers and facilitators impacting the initiation and performance of B-CPR) and context (studies that analysed OHCA emergency calls). Sources of evidence: Medline, CINAHL, Cochrane CENTRAL, Embase, Scopus and ProQuest were searched from inception to 9 March 2022. Charting methods: Study characteristics were extracted and presented in a narrative format accompanied by summary tables. Results: Thirty studies identified factors that impacted B-CPR initiation or performance during the emergency call. Twenty-eight studies described barriers to the provision of CPR instructions and CPR initiation, with prominent themes being caller reluctance (psychological), physical ability (phys- ical), and callers hanging up the phone prior to CPR instructions (communication). There was little evidence examining barriers and facilitators to ongoing CPR performance (2 studies) or CPR quality (2 studies). Conclusions: This scoping review using emergency calls as the source, described barriers to the provision of B-CPR instructions and B-CPR ini- tiation. Further research is needed to explore facilitators and barriers to B-CPR continuation and quality throughout the emergency call, and to exam- ine the effectiveness of call-taker strategies to motivate callers to perform B-CPR.